A paediatric palliative care programme in development: trends in referral and location of death. Issue 9 (7th July 2009) - Vadeboncoeur, C M; Splinter, W M; Rattray, M; Johnston, D L; Coulombe, L
Abstract : Purpose: To describe the formation of a paediatric palliative care programme providing care in hospital, at home or in hospice, ensuring continuity of care where the child and family desire. Study design: Descriptive analysis was performed on referral source, diagnosis and reason for discharge for patients referred to the Palliative Care Team at the Children's Hospital of Eastern Ontario in Ottawa, Ontario, Canada from 1999 to 2007. Results: 341 children were referred. 24% had a neurological condition, 21% had genetic disorders or congenital anomalies, 20% had cancer, 18% had metabolic or neurodegenerative conditions and 17% had another diagnosis. The major sources of referral included paediatricians, neonatologists, oncologists and intensivists. 55% of the children have died. 58% of these died in hospital, 27% at home and 15% in hospice. Of the remaining 152 children, 7% were discharged from the programme after clinical improvement, 4% were moved to another geographic location or an adult centre, 2% were not eligible, 1% declined services and 4% were lost to follow-up. The remaining 90 children continue to be followed-up. In the hospitalised patients who died, the annual referral rate increased from 20% to >50%. Implications: Referral to the palliative care team has increased over time in all diagnostic categories and from all sources. Most children died in hospital; however, a significant number of families chose end-of-life care at home or in a hospice.